Incidental Cardiac Lipoma in a Pediatric Patient - Sebahattin Memis; Mehmet Semih Demirtas (Heart Views)
Cardiac lipomas are primary benign tumors of the heart, consisting mainly of fat cells and the capsule surrounding them. They are rare, usually detected incidentally, and are mostly asymptomatic or may cause symptoms depending on their location. In this case, we planned to present a 13-year-old male patient who was diagnosed with cardiac lipoma, had echocardiography follow-up at regular intervals, and was treated symptomatically. Although cardiac magnetic resonance imaging and histopathological diagnosis are required to confirm the diagnosis of cardiac lipoma, resection may not be necessary due to the location of the mass and the fact that it does not cause any life-threatening symptoms, as in our patient.